2020
DOI: 10.1101/2020.06.05.137364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DUSP7 Regulates the Activity of ERK2 to Promote Proper Chromosome Alignment During Cell Division

Abstract: SUMMARYHuman cell division is a highly regulated process that relies on the accurate capture and movement of chromosomes to the metaphase plate. Errors in the fidelity of chromosome congression and alignment can lead to improper chromosome segregation, which is correlated with aneuploidy and tumorigenesis. Here we show that the dual specificity phosphatase DUSP7 is important for regulating chromosome alignment. DUSP7 bound to ERK2 and regulated the abundance of active phospho-ERK2 through its phosphatase activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It's important to note that protein interactions and associations should be validated biochemically. As examples, we recently used the analytical framework included in CANVS to study the PPI/A networks of DUSP7, which helped to define its regulation of ERK2 during mitosis (Guo et al, 2021), and to analyze the PPA networks of core spindle assembly checkpoint proteins (Garcia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's important to note that protein interactions and associations should be validated biochemically. As examples, we recently used the analytical framework included in CANVS to study the PPI/A networks of DUSP7, which helped to define its regulation of ERK2 during mitosis (Guo et al, 2021), and to analyze the PPA networks of core spindle assembly checkpoint proteins (Garcia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PPI/As can inform on how a POI is compartmentalized within the cell, how it forms higher-order complexes, how it is regulated, and how it coordinates with other proteins to carry out specific cellular processes in a spatial and temporal manner (Yugandhar et al, 2019;Lu et al, 2020). More broadly PPI/A networks have been used to analyze the composition of cellular structures like centrosomes, kinetochores, cilia, and other organelles, and to define the function of cell cycle proteins (Torres et al, 2011;Firat-Karalar and Stearns, 2015;Cheung et al, 2016;Go et al, 2019;Remnant et al, 2019;Garcia et al, 2021;Guo et al, 2021). Several approaches have been used to identify PPIs including yeast two-hybrid (Fields and Song, 1989;Chien et al, 1991), fluorescent resonance energy transfer (Selvin, 1995), and protein fragment complementation assay (Michnick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated evidences demonstrated that lncRNA including SNHG16 and microRNA could regulate the proliferation, invasion, and chemotherapy sensitivity of cancer cells by binding to miRNA and influencing downstream target gene expression. For example, Shi, et al demonstrated that downregulation the expression of microRNA Let-7a-5p, a kind of tumor suppressors, could inhibit the proliferation, migration and invasion of triple negative breast cancer cells [9]; it is reported that overexpression of DUSP7 in breast cancer could increase the drug resistance of breast cancer cells, and overexpression of Let-7a-5p could promote the sensitivity of breast cancer cells to PTX by targeting down regulation of DUSP7 [10,11,12]. Whether SNHG16 participates in PTX resistance of breast cancer cell line MCF-7 cells and the potential mechanism relationships among SNHG16, Let-7a-5p and DUSP7 in PTX resistance to breast cancer cell line were not very clear.…”
Section: Introductionmentioning
confidence: 99%